Mandatory disclosure and asymmetry in financial reporting - Bertomeu, Jeremy; Magee, Robert P. (Journal of Accounting and Economics, 2015)
This paper examines the demand for disclosure rules by informed managers interested in increasing the market price of their firms. Within a model of political influence, a majority of managers chooses disclosure rules with which all firms must comply. In equilibrium, disclosure rules are asymmetric with greater levels of disclosure over adverse events. This asymmetry is positively associated with the informativeness of the measurement and increasing in the level of verifiability and ex-ante uncertainty of the information. The theory also offers implications about the relation between mandatory and voluntary disclosure, when both channels are endogenous.